Between-Person and Within-Person Associations among Processing Speed, Attention Switching and Working Memory in Younger and Older Adults - Stawski, Robert S. (2013)
BACKGROUND/STUDY CONTEXT: Theories of cognitive aging predict associations among processes that transpire within individuals, but are often tested by examining between-person relationships. The authors provide an empirical demonstration of how associations among measures of processing speed, attention switching, and working memory are different when considered between persons versus within persons over time. METHODS: A sample of 108 older adults (M(age): 80.8, range: 66–95) and 68 younger adults (M(age): 20.2, range:18–24) completed measures of processing speed, attention switching, and working memory on six occasions over a 14-day period. Multilevel modeling was used to examine processing speed and attention switching performance as predictors of working memory performance simultaneously across days (within-person) and across individuals (between-person). RESULTS: The findings indicates that simple comparison and response speed predicted working memory better than attention switching between persons, whereas attention switching predicted working memory better than simple comparison and response speed within persons over time. Furthermore, the authors did not observe strong evidence of age differences in these associations either within or between persons. CONCLUSION: The findings of the current study suggest that processing speed is important for understanding between-person and age-related differences in working memory, whereas attention switching is more important for understanding within-person variation in working memory. The authors conclude that theories of cognitive aging should be evaluated by analysis of within-person processes, not exclusively age-related individual differences.